1999
DOI: 10.1002/1529-0131(199905)42:5<989::aid-anr18>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Association of rheumatoid arthritis with a functional chemokine receptor, CCR5

Abstract: Objective. To investigate whether the pathogene-sis of rheumatoid arthritis (RA) is associated with the functional chemokine receptor CCR5, which is the primary CC chemokine receptor expressed by T cells in rheumatoid synovium, and its nonfunctional receptor, 32CCR5, which is generated by the homozygous 32-basepair deletion (32) in the CCR5 gene. Methods. The frequency of the CCR5 genotype was compared among 673 patients with RA, 113 patients with systemic lupus erythematosus (SLE), and 815 control subjects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 15 publications
3
70
1
1
Order By: Relevance
“…T cell activation is thus characterized by increased CCR5 expression, which is associated with diabetes and possibly with other autoimmune diseases. Indeed, CCR5 association is reported in autoimmune diseases such as rheumatoid arthritis [19,20] and multiple sclerosis, in which an increase in CCR5 + cells has been detected [21].…”
Section: Discussionmentioning
confidence: 99%
“…T cell activation is thus characterized by increased CCR5 expression, which is associated with diabetes and possibly with other autoimmune diseases. Indeed, CCR5 association is reported in autoimmune diseases such as rheumatoid arthritis [19,20] and multiple sclerosis, in which an increase in CCR5 + cells has been detected [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on individuals with a variable CCR5 genotype revealed clinical amelioration in RA. In cases in which heterozygosity of the ⌬32 mutation occurred, the patients lacked rheumatoid factor, and the swelling of the joints was decreased compared with wild-type individuals (68,69). In this case, migration to the site of inflammation was reduced.…”
Section: Figurementioning
confidence: 93%
“…21 CCR5 is a coreceptor for the M-tropic strain of human immunodeficiency virus (HIV) and as a result CCR5-D32 homozygotes are afforded complete immunity from this strain, while heterozygotes show resistance to infection and a delay in the onset of acquired immunodeficiency syndrome (AIDS) compared to the wild-type counterparts. [22][23][24][25] In chronic inflammatory disorders, the CCR5-D32 mutation shows a negative association with rheumatoid arthritis, 26 which in turn is associated with a predominantly Th1 immune response. In patients with multiple sclerosis, the mutation is associated with a delayed age of onset of the disease and a lower risk of recurrent clinical disease activity.…”
Section: Introductionmentioning
confidence: 99%